RE:SLAB—a load bearing system for open-ended component reuse in building structures - Estrella, Xavier; Muresan, Alex; Brütting, Jan; Redaelli, Dario; Fivet, Corentin (Frontiers in Built Environment, 2024)
The construction industry plays a major role in the high levels of greenhouse gas emissions, resource consumption, and waste generation observed nowadays. Key to the circular economy, structural component reuse arises as a promising solution to divert construction waste from landfilling and avoid the production of new components. In this context, this paper presents the conceptual design of a new slab-and-column system called "Re:Slab", optimized for disassembly and open-ended reassembly over multiple building lifespans. Beyond conventional considerations of modular sizing and reversible connections, the proposed system provides designers with a minimum kit of parts that is capable of exceptionally diverse building layouts -e.g., related to floor geometry, span between supports, applied loads, and spatial transformations. Attention is given to easily operable assembly and disassembly techniques, embodied environmental impacts, and manufacturing costs. As a result, the proposed system reaches unprecedented high levels of versatility, making it capable of adapting to future functional design requirements that are hard to predict over long-term social developments. Options for increased economic viability are identified, which are necessary to promote widespread adoption of the system.